Improving intelligibility of voiced and voiceless “th” consonants in the speeches of sophomores using pronunciation drills - Maksud Temirov (Jurnal Linguistik Terapan, 2014)
This article is based on a study conducted with the intention of treating a university sophomores’ difficulties in producing intelligible /θ, ð/ sounds and enabling them to achieve faultless pronunciation of these sounds by applying pronunciation drilling technique through authentic teaching sessions. The research design was an Action Research. The subjects were 25 sophomores (4th semester students) of English Department of State University of Malang (East Java, Indonesia). Coming from four different groups (G, GG, H, and J), they formed up a single speaking class at the department. Their ages ranged from 18 to 20. The preliminary study as well as the remedial classes were held on the University campus. The focal instrument of the study was a short text including 12 words each having “th” consonants (/ð/, /θ/ sounds) that was read aloud by the subjects in the preliminary study as well as during and after the teaching sessions. The 3 recordings were carefully analyzed and compiled on a compact disc. The pronunciation drilling technique was implemented in one cycle comprising 4 remedial lessons.The implementation of the action was based on the lesson plans. The researcher himself was the teacher to deliver the remedial lessons through various pronunciation activities such as exercising drills, minimal pair discrimination, tongue-twisters, reading texts on the subjects.The three pronunciation activities were chosen because of the practice in hearing and saying the “th” consonants, moreover, the words containing “th” consonants are pronounced in two ways and the spelling of “th” does not overlap with pronunciation. The assessment of “th” sounds were assessed on whether the sounds were pronounced correctly or not. If one of the sounds, either the voiced “th” or the voiceless one were confusedly pronounced using a different similar or dissimilar sounds instead, such as [d], [t], [f], [s], [z], they were immediately noted down in corresponding tables. However, the correctly pronounced consonants were shown in ticks (ü). The success percentage of each 12 words included in the short text were shown in interactive graphs. The important questions that the researcher decided to deal with were:(1) Can pronunciation drilling technique improve the sophomores’ pronunciation of /θ/ and /ð/ consonants? (2) Can sophomores achieve intelligible pronunciation of /θ/ and /ð/ consonants with ease? The questions were answered with positive results. The students could achieve intelligible production of the two sounds by the end of the study. The findings of this study showed that implementing pronunciation drilling technique when teaching individual sounds, such as /θ/and /ð/ in this case, could make the students achieve rather intelligible pronunciation of English words. Even though several linguists argue that the pronunciation drilling techniques are rather old-fashioned method of teaching pronunciation, based on the results of the present study, however, the researcher believes that this technique is at least useful in teaching individual sounds. Therefore, the speaking class teachers, especially those at secondary schools, have to apply more pronunciation drilling activities in order enable their students achieve an intelligible English pronunciation before they reach the University level. For future researchers, it is suggested to use the result of this study as a reference in conducting researches in the related areas.